Can Dysphagia Following Anterior Cervical Fusions With rhBMP-2 Be Reduced With Local Depomedrol Application?: A Prospective, Randomized, Placebo-Controlled, Double-Blind Trial. Issue 7 (April 2016) - Edwards, Charles C.; Dean, Clayton; Edwards, Charles C.; Phillips, David; Blight, Alexis
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A prospective, randomized, placebo-controlled, double-blind trial. Objective: The aim of this study was to investigate whether the local administration of depomedrol decreases the severity of dysphagia after anterior cervical discectomy and fusion (ACDF) surgery using bone morphogenetic protein (BMP). Summary of Background Data: Although recombinant human BMP-2 is effective in promoting arthrodesis, many physicians avoid using it in anterior cervical spine fusions due to concern for increased incidence of dysphagia, significant pre-vertebral swelling, and airway compromise. Pilot studies have shown that the local application of depomedrol may decrease the incidence of postoperative dysphagia. We performed a prospective, randomized trial to evaluate the efficacy of local depomedrol application in reducing the severity of postoperative dysphagia following anterior cervical fusions using low-dose rhBMP-2. We hypothesized that locally administered depomedrol reduces dysphagia following such surgeries. Methods: Fifty patients between 18 and 70 years of age, undergoing 1, 2, and 3-level ACDFs, were randomized to 1 of 2 groups: BMP-2 with depomedrol or BMP-2 with saline. Patients were followed for 4 weeks postoperatively by the study administrator. Dysphagia was measured at 5 time intervals (postoperative days 1, 4, 7, 14, and 28) using a 4-point Modified Dysphagia Scoring System. Additional data regarding overall length of hospital stay and the administration of dysphagia-directed treatments were also recorded. Results: Twenty-seven patients were randomized to the treatment (depomedrol) group and 23 were randomized to the control (saline) group. The 2 groups were nearly identical in terms of their demographic and operative characteristics. Patients receiving depomedrol experienced decreased dysphagia incidence and magnitude at all time intervals, with differences reaching statistical significance on postoperative days 4, 7, 14, and 28 ( P < 0.05). Conclusion: This study provides Level 1 evidence that locally administered depomedrol on a collagen sponge significantly decreases postoperative dysphagia incidence and magnitude following anterior cervical spine fusion using low-dose rhBMP-2. Level of Evidence: 1